Development and Optimization of Chitosan/ Polyhedral oligomeric Silsesquioxane Nanocomposite Films for Oil Removal Using Box-Behnken Design - Mikhael, Haidy (AUC Knowledge Fountain, 2021)
The solvent casting method was used to prepare nanocomposite membranes made of Chitosan matrix (CS) and Poly(ethylene glycol) Polyhedral oligomeric silsesquioxane (PEG-POSS). The effects of varying PEG-POSS percentage (0-10%) and preparation conditions (homogenization speed (2000-20,000 rpm) and time (5-25 mins)) were studied. The analysis included the change in surface topography and morphology, chemical properties, thermal degradation, tensile strength, porosity, and adsorption capacity of the membranes. The experimental work was designed using Design-Expert software. The responses monitoring and analysis were done using Scanning electron microscopy (SEM), Thermal gravimetric analysis (TGA), Atomic force microscopy (AFM), Fourier-transform infrared spectroscopy (FTIR). The morphological appearance changed, and a rough surface with distinguished topographical features was noted for the PEG-POSS filled samples compared to the pure CS membranes, which gave a smooth appearance and plain surface look. Results indicated that the incorporation of PEG-POSS significantly enhanced the tensile strength, especially for the 0.5% PEG-POSS membranes to around two times the strength of the pure CS membrane. The break point shifted from 3N for the pure CS membrane to 6N for the 0.5% PEG-POSS membrane. Thermal degradation was also greatly affected. A shift in the degradation temperature from 284°C for pure CS to 418°C for the 0.5% PEG-POSS occurred. Moreover, the testing procedure, including membranes immersion in crude oil and water mixtures at pH 6, T 293 K, and contact time 5 mins, confirmed an increase in adsorption capacity from 0.26 mg/gm for the CS only membrane to 2.3 mg/gm for the 0.5% PEG-POSS. The novel nano composite membranes with high tensile strength enhanced thermal durability, and good adsorption capacity can be considered good candidates for crude oil adsorption and removal from water.